A Conrad Chronology - Knowles, O. (Author Chronologies Series, 2014)
Newly revised and enlarged, the second edition of A Conrad Chronology draws upon a rich range of published and unpublished materials. It offers a detailed factual record of Joseph Conrad's unfolding life as seaman and writer as well as tracing the compositional and publication history of his major works.